Investigation of the susceptibility of extended spectrum beta-lactamase (ESBL) producing Escherichia coli and Klebsiella spp. strains to combinations of carbapenems and beta-lactamase inhibitors - Demirda?, Kutbettin; Yüce, Pinar; Özden, Mehmet; Kalkan, Ahmet (My University, 2013)
Objective: Beta-lactamase inhibitor combinations are among to the limited number of agents effective for entended spectrum beta-lactamase (ESBL) strains which cause a considerable health problem worldwide. But the common concern about the ESBLs is the rapid resistance development. We aimed to measure in vitro activity of imipenem, meropenem, and combination of cefoperazone-sulbactam, piperacillin-tazobactam and amoxicillin-clavulanic acid against the ESBL producing Klebsiella and E. coli strains. Material and Method: A total of 300 strain, 230 E. coli, 43 K. pneumoniae and 27 K. oxytoca collected from the inpatients with nosocomial infections admitted to our Institute. ESBL production of the strains were determined by using Double-disk synergy (DDS) test. The susceptibility of the strains against to the studied antibiotics was investigated with broth microdulition method according to the recommendations of NCCLS. Results: No resistance to imipenem and meropenem among E. coli and Klebsiella spp was detected. Susceptibility of E. coli strains to piperacillin-tazobactam, cefoperazone-sulbactam and amoxicillin-clavulanic acid was found as 75.2%, 72.6% and 29.3, respectively. Piperacillin-tazobactam and cephoperazon-sulbactam were determined as equally active as 69.8% to K. pneumoniae strains. Susceptibility of K. oxytoca strains to piperacillin-tazobactam and cephoperazon-sulbactam was found as 55.8% and 40.7%, orderly. The susceptibility of amoxicillin-clavulanic acid among K. pneumoniae and K. oxytoca strains was detected as 23.3% and 18%, respectively. Conclusion: Piperacillin-tazobactam was found relatively more active against ESBL producing E. coli and K. oxytoca strains, than the cefoperazone-sulbactam. Since both antibiotics were found equally sensitive in K. pneumoniae strains they may be used in life-threatening infections when susceptible.
Geni?şlemi?ş spektrumlu beta-laktamaz üreten Escheri?chi?a coli? ve Klebsi?ella spp. suşlarina karşi karbapenemler ve beta-laktam/beta-laktamaz i?nhi?bi?tör kombi?nasyonlarinin duyarlili?inin araştirilmasi
Keywords: Antimicrobial resistance; Beta-lactamase; Escherichia coli; Klebsiella pneumonia